Racism in clinical nursing practice: a qualitative study - Nichole Crenshaw; LaToya Lewis; Cynthia L. Foronda (BMC Nursing)
Abstract Background Racism in healthcare has led to disparate health outcomes amongst people of color. The construct of racism may be misunderstood, and research is lacking about the actions nurses can in the clinical setting take to reduce racism. The purpose of the study was to determine behaviors demonstrative of racism in nursing care and behaviors that are demonstrative of culturally humble nursing care to develop an awareness of racial bias in nursing to inform future educational practices. Methods A qualitative, descriptive design was used with 10 doctoral-prepared nurses of color with expertise in diversity, equity, inclusion, and social determinants of health. Findings Three overarching themes emerged: (1) Experience of Racism as a Nurse of Color (with subthemes of False Assumptions/ Negative Stereotyping, Discrediting/Unheard, and Rejection), (2) Experience of Racism as a Patient of Color (with subthemes of False Assumptions/Negative Stereotyping, Inequitable Treatment/ Lack of Care, and Dismissing/Ignoring or Not Believing), and (3) Culturally Humble Care (with subthemes of Asking, Active Listening, Caring Body Language, Individualized Care, and Respect). Conclusions Study findings may be used to inform and improve nursing practice to reduce racism and decrease health disparities.